Título Padrão - Fonteles Filho, Antônio Adauto; Kurisaka, Seiichi (Arquivos de Ciências do Mar, 2018)
In this paper the authors study some oceanographic conditions in the Caribbean red snapper fishing areas off the Northeast Brazil, and try to establish correlations between each condition and the catch.